North Korea in 1956: reconsidering the August Plenum and the Sino-Soviet joint intervention. Issue 2 (3rd April 2019) - Person, James F.
ABSTRACT: The year 1956 was one of the most pivotal in the history of the North Korean party-state. It marked the end of political diversity and the decline of Soviet and Chinese influence on political, economic, and cultural developments in North Korea. Two incidents in particular, the August Plenum of the Korean Workers' Party, and the joint Sino-Soviet party intervention in a domestic dispute that September, propelled North Korea down the path toward despotism and isolation. Scholars have long suggested that North Korean leader Kim Il Sung faced serious and potentially perilous challenges to his position at the helm of the party-state during these two incidents. Utilising newly available Soviet and Chinese records, this paper challenges the standard narratives of the incidents, and asserts that there was no great threat to Kim's position, either from domestic opposition, or from intervening Soviet and Chinese officials. A fuller understanding of the events of 1956, and of North Korea's construction of a narrative to justify political repression, enables us to better comprehend the nature of the Kim Il Sung regime and its troubled relations with its patron allies throughout the remainder of the Cold War era.